The National Spot Exchange Limited : the sordid saga - Barua, S. K. (SAGE knowledge. Cases., 2016)
The payment crisis at the National Spot Exchange Limited (NSEL) in 2013 was shocking. As investigations revealed, the reasons for the crisis lay in the hubris of the promoters, connivance and collusion of the independent and institutional directors on the board of NSEL, benevolence of the government and ambivalence of the regulator. This case examines the failures at NSEL and raises serious concerns about governance at all levels.